MILLENNIALS’ CAREER DECISION-MAKING DIFFICULTIES (CDMD) IN INDONESIAN UNIVERSITY STUDENTS: MILLENNIALS’ CAREER DECISION-MAKING DIFFICULTIES (CDMD) IN INDONESIAN UNIVERSITY STUDENTS - Murniarti, Erni (Advances in Social Sciences Research Journal, 2019)
Though millennial has unique characteristics as digital natives who prefer to interact with images, branded goods, to have idols and who are interested in modern technological utilization, studying their career decision-making difficulties (CDMD) is barely reported in Indonesia. To respond to such gap, the current report was designed to pattern the CDMD of both male (N = 120) and female (N = 140) undergraduate students in Indonesia. The instrument of the research was totally adopted from Gati et al’s. (1996) career decision-making difficulties questionnaire. Descriptive anaylsis showed that the male (M = 4.93) have higher difficulties than the females (M = 4.85). With different levels of difficulties, the current study, therefore, corresponds to Mau’s (2004), Guan et al’s. (2015), and di Fabio, Palazzeschi, Levin, Levin, and Gati’s (2015) reports.